Emission characteristics and efficiency assessment of biomass-derived syngas in a spark-ignition generator compared to LPG and gasoline - Fredy Surahmanto; Achmad Arifin; Sutiman; Mochamad Syamsiro; Novi Caroko (Results in Engineering)
This study investigates the performance and emission characteristics of biomass gasification-derived syngas under various loads in comparison to Liquefied Petroleum Gas (LPG) and gasoline in a spark-ignition, single-cylinder generator. In the experiment, syngas A (4.11 % CH4, 9.83 % H2, 25.04 % CO, 12.01 % CO2, 49.01 % N2), syngas B (2.88 % CH4, 18.19 % H2, 21.73 % CO, 6.07 % CO2, 51.13 % N2), and syngas C (5.96 % CH4, 18.79 % H2, 28.85 % CO, 8.12 % CO2, 38.28 % N2) were used to represent the real biomass gasification-derived syngas. Engine speed, thermal efficiency, and emissions of CO, CO₂, and HC under variable electrical loads (0–400 W) were analysed. Syngas C delivered the highest lower heating value (7444.13 kJ/kg) and demonstrated superior performance among syngas variants, achieving up to 14.54 % efficiency at 400 W, with CO and HC emissions as low as 0.512 % vol and 15 ppm, respectively. Syngas B performed better at lighter loads due to its high H₂ content, but its efficiency declined with increasing load. In contrast, Syngas A recorded the poorest performance and emissions, including peak CO of 2.112 % and HC of 62 ppm at 200 W. Among the tested fuels, gasoline and LPG exhibited higher CO emissions, reaching 9.56 % and 6.11 % respectively, along with higher HC emissions, particularly for LPG, which reached up to 443 ppm at 0 W load. Despite their lower energy density, syngas fuels, especially Syngas C, showed potential for decentralised, low-to-medium load power generation due to their cleaner emission profile and adequate efficiency.